GEOLOGY OF PONELO REGION AND SURROUNDINGS, NORTH GORONTALO REGENCY - Akase, Noviar; Supriadi, Supriadi (UNM Geographic Journal, 2022)
The research area is one of the islands in the District of Ponelo Islands, North Gorontalo Regency, Gorontalo Province. This study aims to determine the geological conditions of the area using the geological mapping method. The results showed that the geomorphology of the study area was divided into 3 units, namely Lava Flow Hills, Denudasional Hills, and Marin Plains. The stratigraphy of the research area is divided into 5 unofficial units sorted from oldest to youngest, namely Sandstone Unit, Conglomerate Unit, Porphyry Andesite Unit, Basalt Lava Flow Unit (Late Pliocene-Early Pleistocene), and Coastal Sediment Unit (Recent age). The geological structures observed were Shear Fracture, Tension, Sheeting Joint, and Columnar Joint. The geological history of the research area starts from the Late Pliocene to Early Pleistocene where the Lokodidi Formation and Pinogu Volcano Formation were formed, resulting in sandstone and conglomerate units (Lokodidi Formation), porphyry andesite units and basalt lava flow units (Pinogu Volcano Formation). Then the alluvial deposition process which is still ongoing today is the result of weathering of rocks in the research area.